Effect of genetic modification of tyrosine-185 on the proton pump and the blue-to-purple transition in bacteriorhodopsin. - Jang, D J (1990)
The retinylidene chromophore mutant (Y185F) of bacteriorhodopsin, in which Tyr-185 is substituted by phenylalanine, is examined and compared with wild-type bacteriorhodopsin expressed in Escherichia coli; both were reinstituted similarly in vesicles. The Y185F mutant shows (at least) two distinct spectra at neutral pH. Upon light absorption, the blue species (which absorbs in the red) behaves as if "dead"--i.e., neither its tyrosine nor its protonated Schiff base undergoes deprotonation nor does its tryptophan fluorescence undergo quenching. This result is unlike either the purple species (which absorbs in the blue) or wild-type bacteriorhodopsin expressed in E. coli. As the pH increases, both the color changes and the protonated Schiff base deprotonation efficiency suggest a blue-to-purple transition of the Y185F mutant near pH 9. If this blue-to-purple transition of Y185F corresponds to the blue-to-purple transition of purple-membrane (native) bacteriorhodopsin (occurring at pH 2.6) and of wild-type bacteriorhodopsin expressed in E. coli (occurring at pH 5), the protein-conformation changes of this transition as well as the protonated Schiff base deprotonation may be controlled not by surface pH alone, but rather by the coupling between surface potential and the general protein internal structure around the active site. The results also suggest that Tyr-185 does not deprotonate during the photocycle in purple-membrane bacteriorhodopsin.